Youth Policy and Educational Activities in Russian Universities: Stages of Development and Key Contradictions - V. A. Smirnov (Высшее образование в России)
In the context of escalating geopolitical tensions, increasing information confrontation, an important factor in the preservation of the Russian state is systematic activity for the social integration of the younger generation, the development of adequate civic attitudes and values. According to the author of the article, today there is a change in the model of implementation of the state youth policy, the focus of which is increasingly shifting to the education system, including Russian universities. In this regard, an important research task is the analysis of models of youth policy and educational activities in Russian universities. The purpose of the article is a brief overview of the historical models of student education in our country, as well as an analysis of the attitudes of the top management of Russian universities regarding the organization of youth policy and educational activities at the university. The article is based on a series of in-depth interviews conducted with the leadership of Russian universities in July–September 2022. It offers criteria for analyzing the effectiveness of educational work with students, presents a typology of models of such work in Russian universities in different historical periods, highlights the main dysfunctions of youth policy implementation in Russian universities at the present stage. In conclusion, the author proposed several key principles to improve the effectiveness of youth policy and educational activities at the university as an important mechanism for the social integration of the younger generation.